Quantifying Social Value Information Using Analytical Hierarchy Process Method - Choi, Young-Chool; Kang, Ji-Youn; Kim, Hong-Sam; Cho, Kyung-Soon; Lee, Eun-Hee (EAI Endorsed Transactions on Scalable Information Systems, 2023)
This study aims to develop a methodology that can quantify social value at the practical level, considering that it is difficult to quantify the social value information of individual businesses despite the importance of social value both in practice and academia. As people’s living standards rise, the gap between rich and poor has widened, and this phenomenon is broadening the scope of the social welfare projects that central and local governments must carry out. In this context, quantifying the social value information that each project will have is extremely important. However, the reality is that the social value quantification work undertaken in academia has up until now been carried out on an abstract level, because the methodology has not been established. In addition, established social value quantification methodologies embody a problem: it is difficult for policymakers to utilize them, because they represent difficult processes that, in respect of each individual project, require large amounts of professional knowledge, data, time and money if they are to be carried out satisfactorily. Against this background, this study aims to present a single social value quantification methodology that policymakers can employ easily in all circumstances. If the social value quantification method presented in this study, the Analytical Hierarchy Process (AHP) method, is properly applied, then, since it is information and data -based methodology, it should prove meaningful as a practical alternative to existing methods.
Keywords: quantifying social value; AHP; data and information-based methodology